1984
DOI: 10.1172/jci111299
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality of glycophorin-alpha on paroxysmal nocturnal hemoglobinuria erythrocytes.

Abstract: Abstract. To investigate the greater enzymatic activity of the alternative pathway convertase (and the subsequent greater fixation of C3b) on paroxysmal nocturnal hemoglobinuria (PNH) erythrocytes, we have examined the topography of binding of C3b to PNH and normal erythrocytes. Using sodium dodecyl sulfate-polyacrylamide gel electrophoresis and autoradiography, the a-chain of C3b was found to bind via predominantly ester bonds to free hydroxyl groups on glycophorin-a, the major erythrocyte sialoglycoprotein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 68 publications
2
54
1
1
Order By: Relevance
“…26,47 As the signaling events triggered by complement fragments engaging CR1 and GPA have opposing consequences on RBC membrane deformability, the ratio between the number of complement-ligated CR1 and GPA molecules could be important in determining the net change in RBC membrane deformability. Consequently, the genetically determined number of CR1 molecules RBCs could be relevant in certain pathologic conditions associated with significant intravascular complement activation, such as sepsis (reviewed in Markiewski et al 48 ) with high RBC CR1 expressors having functional advantage over the low RBC CR1 expressors.…”
Section: Discussionmentioning
confidence: 99%
“…26,47 As the signaling events triggered by complement fragments engaging CR1 and GPA have opposing consequences on RBC membrane deformability, the ratio between the number of complement-ligated CR1 and GPA molecules could be important in determining the net change in RBC membrane deformability. Consequently, the genetically determined number of CR1 molecules RBCs could be relevant in certain pathologic conditions associated with significant intravascular complement activation, such as sepsis (reviewed in Markiewski et al 48 ) with high RBC CR1 expressors having functional advantage over the low RBC CR1 expressors.…”
Section: Discussionmentioning
confidence: 99%
“…An additional possibility is that another, secondary or primary, defect in the membrane could preclude complete reversal of the lytic abnormality by DAF. For example, the large amounts of in vivo deposited C4 and C3 fragments on the PNH cells (1) or glycophorin abnormalities of the cells (19,20) would not be affected by restoration of DAF and could conceivably influence complement activation on the cell surface. In addition, there is evidence that normal human cell membranes also restrict lysis by homologous complement at the level of C9 (21,22) and that type 3 (23) PNH cells are defective in their resistance to attack by C5b-9.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, DAF could be incorporated into the patients' own cells in vitro, and the autologous cells could be reinjected. However, the bound C4 and C3 fragments or other secondary (or primary) defects (1,19,20,23) in the cells might limit their survival.…”
Section: Discussionmentioning
confidence: 99%
“…1 1). For (11). Recent studies have suggested that glycophorin modulates both sensitivity of cells to reactive lysis (48) and alternative pathway activity (49).…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced convertase activity may be due to several different mechanisms inasmuch as the convertase (a) has greater enzymatic activity when affixed to PNH cells (7), (b) forms more readily on PNH erythrocytes (7,8), and (c) is more stable when bound to the abnormal cell membrane (8,9). These aberrant interactions with complement appear to be related to abnormalities in glycoproteins of the cell surface, which function as regulators of the complement system (8)(9)(10)(11). The greater activity of the C3 convertase is primarily responsible for the enhanced susceptibility of PNH II cells to complement-mediated lysis, because unlike PNH III cells they do not display a marked susceptibility to cytolysis in reactive lysis systems (6).…”
Section: Introductionmentioning
confidence: 99%